A influência dos grupos de referência no processo decisório do consumidor: um estudo no segmento de veículos utilitários esportivos - Sastre, Priscila Tereza de Nadai (2009)
This dissertation had as its general objective to know what types of influence of the reference group relies upon an individual, in his purchase decision process of sports utilitarian vehicles (SUV). The purchase process was assumed as social experiences that individuals make every day and the purchase of products and services is mediated by interpersonal influences. In the marketing field, the relationship between the individual s purchase decision process and the influences received by his social environment has been targeted by relevant discussions in the academic arena, as well as in the corporate world. The theoretical background describes the main constructs of the individual purchase decision process and reference group influence (interpersonal influence), from the American perspective. The justification for this study relies upon the Marketing Science Institute (MSI) priority studies, for the 2006-2008 period. These priorities were formed from research made with the MSI sponsors, who identified the role of social network in the purchase decision process as a priority study in the academic and corporate fields. The methodology approach is the case study method since the investigations aims to explore contemporaneous phenomena from the real life. Among the SUV sellers, in the Brazilian market, Troller, the Ford Motors SUVs subdivision was the one chosen to conduct this research. The data collection started with documents and secondary data of public domain. The empirical verification was supported by self-applied structured questionnaires, distributed electronically for Troller s clients. The results point that the reference group has a significant influence in the Troller s purchase decision process. The informational influence was the main type of influence observed